Effects of continuous positive airway pressure on depression and anxiety symptoms in patients with obstructive sleep apnoea: results from the sleep apnoea cardiovascular Endpoint randomised trial and meta-analysis. (May 2019) - Zheng, Danni; Xu, Ying; You, Shoujiang; Hackett, Maree L.; Woodman, Richard J.; Li, Qiang; Woodward, Mark; Loffler, Kelly A.; Rodgers, Anthony; Drager, Luciano F.; Lorenzi-Filho, Geraldo; Wang, Xia; et al.
Abstract: Background: Whether continuous positive airway pressure (CPAP) treatment can improve depression or anxiety symptoms in obstructive sleep apnoea (OSA) patients remains uncertain. Methods: Secondary analysis of the Sleep Apnea Cardiovascular Endpoints (SAVE) trial, combined with a systematic review of randomised evidence. The SAVE secondary analyses involved 2410 patients with co-existing moderate–severe OSA and established cardiovascular disease randomly allocated to CPAP treatment plus usual care or usual care alone and followed up for 3·7 (SD 1·6) years. We evaluated the effect of CPAP treatment on depression and anxiety caseness (scores ≥ 8 on the Hospital Anxiety and Depression Scale depression and anxiety subscales [HADS-D and HADS-A]) for OSA patients. Findings: CPAP treatment was associated with reduced odds of depression caseness (adjusted odds ratio [OR] 0·80, 95% confidence interval [CI] 0·65–0·98, P = 0·031) compared to usual care in the SAVE trial and the treatment effect was greater in those with pre-existing depression symptoms. A systematic review of 20 randomised trials including 4255 participants confirmed a benefit of CPAP in reducing depression symptoms in OSA patients: the overall effect (standardised mean difference) was − 0·18 (95% CI − 0·24 to − 0·12). No effect of CPAP treatment on anxiety caseness was found both in patients of the SAVE study (adjusted OR 0·98, 95% CI 0·78–1·24, P = 0·89) and the systematic review. Interpretation: CPAP reduces depression symptoms in patients with co-existing OSA and CVD independently of improvements in sleepiness. Highlights: Depression and anxiety are prevalent in patients with chronic conditions, such as obstructive sleep apnoea (OSA) and cardiovascular disease, and they adversely impact on prognosis and quality of life. Whether continuous positive airway pressure (CPAP) treatment can improve depression or anxiety symptoms in OSA patients still remains uncertain. We searched PubMed for studies in English language published before 1 Jan 2019 reporting of CPAP effect on depression and anxiety symptoms using the terms "continuous positive airway pressure", "obstructive sleep apnoea", "depression" and "anxiety". A recent systematic review of randomised trials on the effect of CPAP on depression symptoms had found modest benefit of CPAP treatment for improving depression symptoms, however there was high heterogeneity. Existing findings are variable across studies due, in part, to different study designs, small patient numbers, short periods of follow-up, and from an emphasis on depression over anxiety patterns of abnormal mood. Added value of this study: Analysis of the Sleep Apnea Cardiovascular Endpoints (SAVE) cohort of over 2400 patients with moderate to severe OSA and concomitant cardiovascular diseases who were followed up for an average of 3.7 years showed that the CPAP reduced depression symptoms within few months of treatment, independently of improvements in daytime sleepiness. The NNT (i.e. 15) for CPAP to prevent depression caseness (as defined by Hospital Anxiety and Depression Scale – Depression subscale score ≥ 8) is comparable to remission rates achieved for some established antidepressant drugs. However, analyses of the SAVE study showed no clear clinical benefit for anxiety symptoms. Systematic review of 20 included randomised controlled studies showed similar results as our SAVE secondary analyses. Implications of all the available evidence : Our findings provide further support for the broader beneficial effects of CPAP in those with OSA, and especially those at high cardiovascular risk, where there is the potential for enhanced mood to improve long-term cardiovascular outcomes.